Method Development And Validation For The Simultaneous Estimation Of Cabotegravir And Rilpivirine In Bulk And Pharmaceutical Dosage Form And Stability Studies By Uplc (International Journal of Food and Nutritional Sciences, 2022)
A simple, Accurate, precise method was developed for the simultaneous estimation of the Cabotegravir and Rilpivirine in pharmaceutical dosage form. Chromatogram was run through Hibar C18 100 x 2.1 mm, 2m. Mobile phase containing Water: Acetonitrile taken in the ratio 55:45 was pumped through column at a flow rate of 0.3 ml/min. Temperature was maintained at 30°C. Optimized wavelength selected was 257 nm. Retention time of RPN and CGV were found to be 0.618 min and 1.152. %RSD of the CGV and RPN were found to be 0.3 and 1.5 respectively. %Recovery was obtained as 99.79% and 99.58% for CGV and RPNrespectively. LOD, LOQ values obtained from regression equations of CGV and RPN were 0.43, 1.30 and 0.78, 2.37 respectively. Regression equation of CGV is y = 4028.3x + 977.59, and RPN is y = 4057.2x + 1673.2. Retention times were decreased and that run time was decreased, so the method developed was simple and economical that can be adopted in regular Quality control test in Industries.